2009
DOI: 10.1016/j.cmet.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 Regulates Pancreatic β Cell Size, Polarity, and Function

Abstract: Summary Pancreatic β cells, organized in the islets of Langerhans, sense glucose and secrete appropriate amounts of insulin. We have studied the roles of LKB1, a conserved kinase implicated in the control of cell polarity and energy metabolism, in adult β cells. LKB1-deficient β cells show a dramatic increase in insulin secretion in vivo. Histologically, LKB1-deficient β cells have striking alterations in the localization of the nucleus and cilia relative to blood vessels, suggesting a shift from hepatocyte-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
166
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(188 citation statements)
references
References 59 publications
19
166
3
Order By: Relevance
“…The primary cilia were projected from the Golgi region to intercellular spaces and their basal part was usually surrounded by deep invaginations of the plasma membrane. In an immunostaining of mouse pancreatic islets with an antibody against acetylated tubulin, the primary cilia were mostly localized in the lateral surface of B cells away from capillaries (9), in agreement with the present SEM study. It is generally believed that somatostatin released from pancreatic D cells is conveyed by local blood circu-ence of primary cilia on B cells.…”
Section: Discussionsupporting
confidence: 79%
“…The primary cilia were projected from the Golgi region to intercellular spaces and their basal part was usually surrounded by deep invaginations of the plasma membrane. In an immunostaining of mouse pancreatic islets with an antibody against acetylated tubulin, the primary cilia were mostly localized in the lateral surface of B cells away from capillaries (9), in agreement with the present SEM study. It is generally believed that somatostatin released from pancreatic D cells is conveyed by local blood circu-ence of primary cilia on B cells.…”
Section: Discussionsupporting
confidence: 79%
“…LKB1 depletion uncouples glucose metabolism from calcium influx and insulin secretion We and others previously reported that deletion of Lkb1 in adult mouse beta cells leads to increased insulin secretion [19,26]. Here, we report that LKB1 acts to attenuate K ATP channel closure and calcium influx.…”
Section: Discussionmentioning
confidence: 62%
“…However, targeting liver kinase B1 (LKB1) in the beta cell for the treatment of diabetes would be undesirable as knockout of Lkb1 in adult mice has a deleterious effect on haematopoietic stem cell maturation [20][21][22]. We and others have identified non-overlapping functions in beta cells for LKB1 targets, including MAP/microtubule affinityregulating kinase 2 (MARK2), salt-inducible kinase 2 (SIK2), brain-specific kinase 2 (BRSK2) as well as AMPactivated protein kinase (AMPK) itself [19,[23][24][25][26][27][28], underscoring the potential for identifying the minimal target(s) of LKB1 responsible for enhancing insulin secretion. Here, we systematically interrogated insulin secretion pathway components to identify the signals responsible for enhanced insulin secretion in Lkb1 knockout islets.…”
Section: Introductionmentioning
confidence: 99%
“…cell proliferation was enhanced in islets from mice in which the expression of both AMPK catalytic subunits was ablated selectively in pancreatic cells (26). In contrast, islets of Langerhans from mice in which the expression of an AMPK upstream kinase liver kinase B1 (LKB1) was ablated, had increased islet and cell size (181) and altered islet architecture (181)(182)(183)(184). Thus, the number of large islets, which may account for as much as 50 % of the total pancreatic cell mass in normal pancreata (185), was increased in pancreata from mice in which LKB1 expression was selectively ablated in the cell (181).…”
Section: Ampk and Lkb1mentioning
confidence: 99%